Mechanical Properties of Polypropylene Macrofiber-Reinforced Concrete - Zhishu Yao; Xiang Li; Cao Fu; Weipei Xue (Advances in Materials Science and Engineering)
To economically and reasonably solve the difficult problem of mine shaft support subject to complex geological conditions, we studied the mechanical properties of polypropylene macrofiber-reinforced concrete (PPMFRC). First, we selected test raw materials through an investigation and comparison of technical parameters. Second, using a preparation test, we obtained the composition of reference concrete of PPMFRC for the mine shaft lining structure, and test specimens were manufactured according to relevant test technical regulations. Finally, the mechanical properties of the specimens were compared, and the results show that the compressive, flexural, and tensile strengths of PPMFRC were increased by approximately 3%, 30%, and 20%, respectively, for mixtures with polypropylene macrofibers. The fracture toughness of PPMFRC was between 0.26 and 0.35, and the fracture energy was between 382.7 N/m and 485.6 N/m, which is significantly higher than that of plain concrete. The test results show that PPMFRC is an ideal material for the lining structure of a mine shaft under complex geological conditions, and we have provided technical parameters for engineering applications.